2006
DOI: 10.1038/sj.ejcn.1602512
|View full text |Cite
|
Sign up to set email alerts
|

Wild berries: a good source of omega-3

Abstract: It has been reported that some wild green vegetables are good sources of a-linolenic acid (ALA, an essential omega-3 fatty acid). Using available data from the Norwegian food composition table, the present study shows that three common Nordic berries (blueberry, cloudberry and cowberry) on average contain 0.7 g of fat ( ¼ 21% of total energy) and 0.25 g ALA ( ¼ 36% of total fat) per 100 g, which is quite similar to what has been reported for the ALA-rich wild green vegetables. In addition, this study shows tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 7 publications
1
29
0
1
Order By: Relevance
“…Accordingly to United State Department of Agriculture (USDA) National Nutrient Database for Standard Reference (http://www.nal.usda.gov/fnic/food comp/search/), cranberries (Vaccinium macrocarpon) are largely constituted of water (87% w/w) with carbohydrates accounting for approximately the balance of its weight (12% ; Table 1). Despite not having an important fat content, the high proportion of n-3 long-chain fatty acids in berries makes them an important proportion of the daily intakes in some populations [61]. The list of other macro and micronutrients found in cranberries is also shown in Table 1.…”
Section: Cranberry Compositionmentioning
confidence: 99%
“…Accordingly to United State Department of Agriculture (USDA) National Nutrient Database for Standard Reference (http://www.nal.usda.gov/fnic/food comp/search/), cranberries (Vaccinium macrocarpon) are largely constituted of water (87% w/w) with carbohydrates accounting for approximately the balance of its weight (12% ; Table 1). Despite not having an important fat content, the high proportion of n-3 long-chain fatty acids in berries makes them an important proportion of the daily intakes in some populations [61]. The list of other macro and micronutrients found in cranberries is also shown in Table 1.…”
Section: Cranberry Compositionmentioning
confidence: 99%
“…Berries are known to contain high amounts of vitamins, phenolic compounds, trace elements and fiber, as well as beneficial fatty acid composition (Kalt et al, 1999;Kallio et al, 2002;Määttä-Riihinen et al, 2004;Bere, 2007). A daily amount of 155 g of mixed berries has been shown to improve some factors associated with cardiovascular health and thus possibly to reduce the risk of vascular problems (Erlund et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Lingonberry also contains condensed tannins, called proanthocyanidins (Chung et al, 1998) led lignans (10-15 mg/kg dry weight whereas more than 116 anthocyanins and flavonoids compounds have been isolated and identified primarily from the fruits or leaves (Kalt et Bere (2007) noticed, that n 3 fatty acids were present in lingonberry, in 0.14 respectively 0.18 g/100g concentration. According to .…”
Section: Vaccinium Vitis Idaeamentioning
confidence: 99%
“…(2003), the main acids of the northern region rry juices are citric and malic acids, while juice of n benzoic acid in amount of 0.1 case of lingonberry, it is the benzoic acid concentration which is especially high (up to 1.3 g/l free benzoic acid) Thus, evaluating the antimicrobial efficacy of phenolic compounds either in food matrices or in pH was a very important parameter to be . It was demonstrated that lingonberry may affect the activity of several human pathogenic and food spoilage bacteria (Caillet Several Bere (2007) noticed, that n 3 fatty acids were present in lingonberry, in 0.14 respectively 0.18 g/100g concentration. According to .…”
Section: Vaccinium Vitis Idaeamentioning
confidence: 99%